2014
DOI: 10.1007/s11033-014-3075-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in hypothalamus of chicken during cold stress

Abstract: In order to discover the mechanism of cold stress and identify differentially expressed genes in hypothalamus during cold stress, 4 weeks of age Huainan partridge chickens, Chinese indigenous breed, were chosen for 24 h cold stress and then hypothalamus were isolated and labeled by reverse transcription reaction for cDNA. Labeled cDNA were hybridized with cDNA microarray. After scanning and image processing, the different gene expression profiling of hypothalamus and normal control was investigated. The differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Low and high environmental temperatures are the most challenging stressors impacting both poultry and livestock industries. Cold stress, for instance, has been reported to cause an estimated total annual economic loss to the Chinese poultry industry of 100 million in currency [ 5 ]. A tremendous amount of seminal work has been done to identify the animal physiological and behavioral responses to cold stress and improve management strategies, however, the underlying molecular mechanisms are still not completely defined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Low and high environmental temperatures are the most challenging stressors impacting both poultry and livestock industries. Cold stress, for instance, has been reported to cause an estimated total annual economic loss to the Chinese poultry industry of 100 million in currency [ 5 ]. A tremendous amount of seminal work has been done to identify the animal physiological and behavioral responses to cold stress and improve management strategies, however, the underlying molecular mechanisms are still not completely defined.…”
Section: Discussionmentioning
confidence: 99%
“…These neuropeptides interact in a complex way with each other and with the central melanocortin system, melanin-concentrating hormone, orexin, ghrelin and adiponectin, to mention a few, to regulate energy homeostasis in mammals [for review see [ 47 ]]. A recent study, using microarray analysis, reported 24h-cold exposure-induced changes in chicken hypothalamic gene expression [ 5 ]. Our work complements and adds to this study by showing that CMCC down regulated the expression of the potent orexigenic NPY and anorexigenic CART genes which may explain the similar feed intake observed between the control and CMCC chicks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, several meaningful KEGG pathways that are associated with energy homeostasis and lipid metabolism were significantly enriched, such as adipocytokine signaling, cAMP signaling, and fatty acid biosynthesis. Interestingly, the neuroactive ligandreceptor interaction is initiated in chickens to stimulate the central nervous system for feed intake under cold stress conditions (Chen et al 2014). From the significant KEGG pathways, we inferred that the adaptable genes induced the energy homeostasis to respond to the relatively high energy demand under heat stress conditions.…”
Section: Deg Patterns and Functional Enrichmentmentioning
confidence: 96%